2020
DOI: 10.1080/20013078.2020.1795365
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of extracellular vesicle‐based treatments for lung injury: are EVs a potential therapy for COVID‐19?

Abstract: Severe COVID-19 infection results in bilateral interstitial pneumonia, often leading to acute respiratory distress syndrome (ARDS) and pulmonary fibrosis in survivors. Most patients with severe COVID-19 infections who died had developed ARDS. Currently, ARDS is treated with supportive measures, but regenerative medicine approaches including extracellular vesicle (EV)-based therapies have shown promise. Herein, we aimed to analyse whether EV-based therapies could be effective in treating severe pulmonary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 117 publications
1
69
0
1
Order By: Relevance
“…Regardless of which method used to isolate and concentrate EVs each method requires standardization in order to optimize reproducibility, purity, and maintenance of EVs' functional properties (Gardiner et al 2016;Khalaj et al 2020).…”
Section: Isolation Purification and Productionmentioning
confidence: 99%
“…Regardless of which method used to isolate and concentrate EVs each method requires standardization in order to optimize reproducibility, purity, and maintenance of EVs' functional properties (Gardiner et al 2016;Khalaj et al 2020).…”
Section: Isolation Purification and Productionmentioning
confidence: 99%
“…In a systematic review, Khalaj et al [ 198 ] reported that exosomes extracted from mesenchymal stem cells derived from bone marrow or umbilical cord ameliorate lung injury in experimental models by (1) attenuating inflammation (reducing pro-inflammatory cytokine levels, neutrophil infiltration, and macrophage polarization); (2) regenerating alveolar epithelium (by reducing apoptosis and stimulating surfactant production); (3) reducing microvascular permeability (by upregulating endothelial cell junction protein levels); and (4) preventing fibrosis (reducing fibrin production). The authors attributed these differential effects to the release of EV cargoes and identified several of the factors responsible, which included miRs126, -30b, -3p, -145, -27a-3p, syndecan-1, hepatocyte growth factor, and angiopoietin-1 [ 198 ]. Exosomal delivery of miR-146b inhibited tumor growth in a xenograft model of GBM [ 161 , 199 ], and the delivery of anti-miRs against miR-9 (an oncogenic miRNA) to GBM cells increased their susceptibility to chemotherapeutics like temozolomide [ 160 ].…”
Section: Exploiting Exosomes For Therapeuticsmentioning
confidence: 99%
“…The majority of the reported effects, namely restoration of epithelial and endothelial function by increased cellular repair and decreased rate of apoptosis, higher surfactant production, increased resorption of lung fluid, restoration of tight junctions and reduced fibrin production may be mediated by EVs. EVs are also supposed to be involved in reduction of pro-inflammatory and enhancement of anti-inflammatory cytokine secretion, reduction of neutrophil infiltration and M2 polarization of alveolar macrophages [ 41 ]. Preclinical data identified cell-to-cell contact via programmed death-1 for MSC-T cell interaction, changes in amino acid and lipid metabolism by indoleamine 2,3-dioxygenase (IDO) expression, prostaglandin E2 (PGE2) production, tumor growth factor-beta (TGF-β) and HGF and increased expression of leukocyte protease inhibitor via EGF and HGF as important mechanisms [ 42 ].…”
Section: Types Of Mscs and Msc-derived Productsmentioning
confidence: 99%